MHC Class I Quality Control - Mora-Herrera, Martha E.; Lopez-Delgado, Humberto; Valadez-Moctezuma, Ernestina; Scott, Ian M.; Roder, Gustav; Geironson, Linda; Follin, Elna; Thuring, Camilla; Paulsson, Kajsa (IntechOpen, 2012)
None